Effect of Single-session Solution-focused Brief Therapy on the Anxiety of Labor Pain: A Randomized Clinical Trial - Mahdie Mohiti; Shahrbanoo Salehin; Ali mohammad Nazari; Shahrbanoo Goli; Maryam Zamani (Mashhad University of Medical Sciences, 2022)
Background: Anxiety of labor pain can affect new mothers' mental health and lead to labor dystocia. Emotional support during pregnancy and childbirth has been reported to be effective in the reduction of labor anxiety. It seems that Solution-Focused Brief Therapy (SFBT) would be the practical method for minimizing the anxiety and pain during labor.Aim: This study aimed to investigate the effect of SFBT on anxiety and labor pain in nulliparous women.Method: This randomized clinical trial was implemented on 110 nulliparous pregnant women, who could not attend childbirth preparation classes due to the COVID-19 pandemic at Hakim Hospital, Neyshabur, Iran, from September to December 2020. The sampling was conducted using the Convenience method, and block randomization was employed for the random allocation of two intervention and control groups. The intervention group received single-session SFBT in a personal counseling session, and the control group received routine care, including heat water bags and aromatherapy. The data were collected using a demographic characteristics questionnaire, Spielberger anxiety inventory, and visual analog scale. A P-value less than 0.05 was considered statistically significant.Results: There were significant differences between stages regarding the mean scores of labor pain and anxiety (P<0.001, P<0.001). The interaction of group and stages (P=0.002, P=0.003) and the independent effect of the group were also significant (P<0.001, P<0.001).Implications for Practice: The SFBT approach could reduce anxiety and labor pain in nulliparous women who do not participate in childbirth preparation classes.